Incidence of fern contamination in nodal segment cultures of Shorea parvifolia dyer - Mohd Yusof, Aziah; Ab Shukor, Nor Aini; Awang, Kamis; Abdul Kadir, Mihdzar (Universiti Putra Malaysia Press, 2013)
The greatest drawback in large scale micropropagation of tropical woody forest species is high contamination of cultures. In developing a sterilization protocol for micropropagation of Shorea parvifolia Dyer utilizing nodal segments excised from nursery-grown seedlings, it was found that washing 20% (v/v) with Clorox solution for 18 minutes was the best. After six weeks of culture in WPM media supplemented with 10-5 M BAP (apart from fungal and bacterial contamination), the nodal segments developed hair-like structures which were amenable to subculture. Upon subculture, green leafy structures developed from the mass of hairy structure after six weeks. These later developed into ferns which are normally found as epiphytes on older forest trees, known as Asplenium nidus.